Mixture formation and combustion characteristics of diesel-hydrogen dual fuel engine - Widodo Budi, Santoso (2016)
Among the alternative fuels, hydrogen shows great potential as fuel and energy carrier. The advantages of using hydrogen as fuel for internal combustion engine is amongst other a long-term renewable and less polluting fuel, non-toxic, odourless, and has wide range flammability. This thesis deals with the utilization of hydrogen as fuel for diesel engine under dual fuel operation. Hydrogen is mixed with air or injected in the intake manifold before entering combustion chamber. Small amount of diesel fuel is injected to promote ignition. A modified experimental setup based on a single cylinder direct injection diesel engine together with 3D computational model was employed. The model incorporates detailed chemical kinetics for the oxidation of hydrogen and diesel fuel represented by the primary reference fuel consists of n-heptane and isooctane. During the combustion processes, the turbulence-chemistry interaction was accounted for. In the experimental part of this study, the effects of introducing hydrogen in varying flow rates on engine performance, combustion, and emission in the DI diesel engine were investigated. The corresponding results were further used to validate the simulation model. The simulation provides the mean calculation results and also the spatial and temporal distributions of temperature, cylinder pressure, velocity, and species mass fractions which are key data for the interpretation of the combustion processes. Experimental results showed that hydrogen addition at certain flow rate gave a different influence on the combustion, depending on the amount of the pilot diesel fuel or the engine load. Hydrogen addition at the low load reduced the cylinder pressure. On the other hand, it increased the cylinder pressure at higher loads. Simulation revealed that for the same hydrogen flow rate, higher load resulted in a faster combustion and earlier start of ignition. Hydrogen percentage of about 70 % based on energy sharing would be the maximum amount for a good combustion efficiency and stability. In depth investigation by simulation showed that the burning of hydrogen-air mixtures essentially occurs around the regions in the vicinity of the spray with high temperature. When diesel fuel vapour reached its flammability limit at high temperature, the ignition started. Hydrogen-air mixture oxidized at some degree crank angle after the commencement of the ignition. Fast combustion was observed during the diesel oxidation. When most of pilot diesel fuel has been oxidized, the combustion became slower. Hydrogen-air mixture oxidation was mainly due to flame propagation until the end of expansion stroke. The amount of the hydrogen that can be converted into the combustion products seems to be defined by the amount of the diesel pilot fuel. Some valuable insight and new ideas were identified through the extensive experimental and numerical investigation into the diesel-hydrogen dual fuel engine. Incorporating a detailed pilot fuel injection model which can provide more accurate results for pilot injection, developing an improved kinetic model for dual fuel combustion processes with gaseous fuel as the main fuel, and developing an improved heat transfer model which suit for dual fuel combustion are amongst area of future research.